Serum gamma-glutamyltransferase and alkaline phosphatase in rheumatoid arthritis. Issue 6 (June 1982) - Spooner, R J; Smith, D H; Bedford, D; Beck, P R
Abstract : Serum gamma-glutamyltransferase (GGT) and alkaline phosphatase (AP) were assayed in 98 consecutive patients with rheumatoid arthritis. Twenty-three patients had increased GGT activities and 45 an increased AP activity. Twelve patients showed an increase in both enzyme activities and AP isoenzyme studies were performed on seven of this group. In three subjects an increase in the bone isoenzyme was observed and in three others the increase in activity was attributed to the liver isoenzyme. The remaining patient, who probably suffered from coexistent primary biliary cirrhosis, showed an increase in both bone and liver isoenzymes. The liver involvement, suggested by the alkaline phosphatase isoenzyme results, was largely confirmed by the butanol extraction of GGT. The changes in these enzymes in this small series could not be related definitely to drug therapy. It is concluded that though increases in GGT and AP are common in rheumatoid arthritis, this does not necessarily indicate hepatic involvement. Further isoenzyme studies are needed to define the extent to which organs other than the liver bring about increases in these serum enzymes in rheumatoid disease.